Sticks and Stones: The Effects of Teasing on Psychosocial Functioning in an Overweight Treatment-seeking Sample - Quinlan, Nicole P. (Soc Dev, 2009)
This self-report and observational study explores the relationship between perceptions of different kinds of teasing experiences and psychosocial functioning in an overweight treatment-seeking adolescent population. Participants were 96 adolescents enrolled in a residential weight-loss camp program. Prior to the start of treatment, participants’ weight status was measured by trained program staff, and participants’ perceptions of teasing experiences and psychosocial functioning were assessed through self-report questionnaires. Controlling for body mass index, more frequent and upsetting weight-related teasing experiences were associated with worse psychological functioning. Adolescents most distressed by weight-related teasing exhibited lower self-esteem and higher depressive symptoms regardless of reported frequency of weight-related teasing. Competence-related teasing was also associated with more worries about weight, greater depressive symptoms, and more negative anti-fat attitudes. Weight-related teasing, but not competence-related teasing, was associated with lower levels of program and social involvement for heavier adolescents.